2014
DOI: 10.1227/neu.0000000000000328
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality in the Surgery of Cerebral Aneurysms

Abstract: Augmented reality may add to the performance of a minimally invasive approach, although further studies need to be performed to evaluate whether certain groups of aneurysms are more likely to benefit from it. Further technological development is required to improve its user friendliness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 21 publications
(26 reference statements)
0
96
0
2
Order By: Relevance
“…These systems allow overlaying 3D projections derived from preoperative surgical images into bilateral eyepieces of the binocular optics of the operating microscope, precisely aligned with the surgical field. [22,11,4,3,5,38,16,34] To achieve a coherent fusion between real images and virtual content, these systems monitor microscope optics pose, focus, zoom, and all internal camera parameters. [13] This is an important advantage as other, simpler, systems require manual alignment with the surgical field.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These systems allow overlaying 3D projections derived from preoperative surgical images into bilateral eyepieces of the binocular optics of the operating microscope, precisely aligned with the surgical field. [22,11,4,3,5,38,16,34] To achieve a coherent fusion between real images and virtual content, these systems monitor microscope optics pose, focus, zoom, and all internal camera parameters. [13] This is an important advantage as other, simpler, systems require manual alignment with the surgical field.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, perception localization on the patient is much more intuitive. The goal can be achieved both by the unaided eye,[2] or by devices presenting the AR scene in the line of view between the surgeon and the surgical field, as in the case of the microscope,[4,3,5,16,38] the tablet,[8] and the light field display. [15]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Augmented reality can be described as live direct or indirect view of a physical real-world environment whose elements are augmented by computer generated sensory input such as sound, video, graphics, or GPS data [1,2,4,5]. One's current perception of reality can be enhanced by the functions of this technology.…”
Section: Methodsmentioning
confidence: 99%
“…5 It seems a logical consequence to use it also for improving registration accuracy. In fact, Cabrilo et al 5 suggested exactly that.…”
Section: Rationale Of the Proposed Techniquementioning
confidence: 99%